2019
DOI: 10.3389/fpls.2019.00470
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of Salinity Stress in Plants by Arbuscular Mycorrhizal Symbiosis: Current Understanding and New Challenges

Abstract: Modern agriculture is facing twin challenge of ensuring global food security and executing it in a sustainable manner. However, the rapidly expanding salinity stress in cultivable areas poses a major peril to crop yield. Among various biotechnological techniques being used to reduce the negative effects of salinity, the use of arbuscular mycorrhizal fungi (AMF) is considered to be an efficient approach for bio-amelioration of salinity stress. AMF deploy an array of biochemical and physiological mechanisms that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
194
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 386 publications
(275 citation statements)
references
References 178 publications
(257 reference statements)
8
194
0
3
Order By: Relevance
“…It was confirmed that the P5CS plays a major role in proline biosynthesis under salt stress in both salt tolerant PBG-5 and salt sensitive CSG-9505 genotypes of chickpea (Jahromi et al, 2008;Garg and Baher, 2013). Free proline and total soluble sugars are the major osmolytes in AMF-inoculated plants under salt stress that control the osmotic potential at the cellular level, leading to enhanced salt tolerant ability (Campanelli et al, 2013;Yang et al, 2014;Evelin et al, 2019). Free proline enrichment in the salt stressed plants with AMF inoculation plays a key role as osmotic adjustment (Chun et al, 2018), which confirmed the function as osmolytes by mitigation of NaCl stress in mustard plant (Sarwat et al, 2016).…”
Section: Soluble Sugar Free Proline Osmotic Potential and Their Rementioning
confidence: 84%
See 1 more Smart Citation
“…It was confirmed that the P5CS plays a major role in proline biosynthesis under salt stress in both salt tolerant PBG-5 and salt sensitive CSG-9505 genotypes of chickpea (Jahromi et al, 2008;Garg and Baher, 2013). Free proline and total soluble sugars are the major osmolytes in AMF-inoculated plants under salt stress that control the osmotic potential at the cellular level, leading to enhanced salt tolerant ability (Campanelli et al, 2013;Yang et al, 2014;Evelin et al, 2019). Free proline enrichment in the salt stressed plants with AMF inoculation plays a key role as osmotic adjustment (Chun et al, 2018), which confirmed the function as osmolytes by mitigation of NaCl stress in mustard plant (Sarwat et al, 2016).…”
Section: Soluble Sugar Free Proline Osmotic Potential and Their Rementioning
confidence: 84%
“…Previous studies have reported a positive relationship between AMF symbiosis and salt defense mechanisms of the host plants (Ruiz-Lozano and AzcĂłn, 2000). For example, ion homeostasis (influx/efflux), compartmentalization (vacuolar storage), and Na + translocation from root to shoot via apoplastic and/or symplastic routes have been regulated by AMFinoculation (Evelin et al, 2009;Porcel et al, 2012;He and Huang, 2013;Porcel et al, 2016;Yadav et al, 2017;Evelin et al, 2019). Better defense responses in terms of the higher production of free proline, glycine betaine, and soluble sugars in AMF inoculated plants against salt stress have also been reported (Campanelli et al, 2013;Evelin et al, 2013;Garg and Baher, 2013;Talaat and Shawky, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…At the molecular level, the elucidation of the mechanisms implicated in AMF symbiosis under salt stress has advanced over the past decade [60][61][62][63][64]. The stress perception is channelized inside the nucleus, resulting in the expression of multiple stress-responsive genes, related to cellular protection against the stress (e.g., antioxidants, late embryogenesis abundant proteins and chaperons) or implicated on the perception, transmission and transcription of the signal [38,60,61]. Recent studies revealed the molecular mechanisms of high K + /Na + ratio in mycorrhizal plants, which are based on the induced expression of genes involved in K + acquisition and Na + extrusion to the soil [61][62][63][64].…”
Section: Arbuscular Mycorrhizal Fungi (Amf)mentioning
confidence: 99%
“…The stress perception is channelized inside the nucleus, resulting in the expression of multiple stress-responsive genes, related to cellular protection against the stress (e.g., antioxidants, late embryogenesis abundant proteins and chaperons) or implicated on the perception, transmission and transcription of the signal [38,60,61]. Recent studies revealed the molecular mechanisms of high K + /Na + ratio in mycorrhizal plants, which are based on the induced expression of genes involved in K + acquisition and Na + extrusion to the soil [61][62][63][64]. For example, in Oryza sativa L., up-regulation of OsNHX3 (sodium/hydrogen exchanger) by AMF allows the compartmentalization of Na + into the vacuole [63].…”
Section: Arbuscular Mycorrhizal Fungi (Amf)mentioning
confidence: 99%
“…Other benefits include increased reproductive success and/ or tolerance to (a)biotic stresses. Several of the above effects are finely regulated by phytohormones, via a limitedly understood and highly context dependent interaction (Gutjahr, 2014;Selosse, Bessis & Pozo, 2014;Pozo et al, 2015;Lenoir, Fontaine & Sahraoui, 2016;Bedini et al, 2018;Liao et al, 2018;Cabral et al, 2019;Evelin et al, 2019).…”
Section: Introductionmentioning
confidence: 99%